The Pharmacogenomics of Anti-Hypertensive Therapy - Sandosh Padmanabhan; Laura Paul; Anna F. Dominczak (Pharmaceuticals, 2010)
Hypertension is a major public health problem, but measures to reduce blood pressure and thus cardiovascular risk are complicated by the high prevalence of treatment resistance, despite the availability of multiple drugs. Drug side-effects contribute considerably to suboptimal blood pressure control. Clinicians must often rely on empirical methods to match patients with effective drug treatment. Hypertension pharmacogenomics seeks to find genetic predictors of response to drugs that lower blood pressure and to translate this knowledge into clinical practice. In this review we summarise the current status of hypertension pharmacogenetics from monogenic hypertension to essential hypertension and discuss the issues that need to be considered in a hypertension pharmacogenomic study.